Impact of Training & Development and Career Planning on Employee Involvement - Dr. Gopal Man Pradhan; Dr. Prakash Shrestha (Journal of Balkumari College, 2022)
The purpose of this research is to investigate the impact of training and development as well as career planning in Nepalese service sector organizations. Data for this study were gathered from service organizations such as banks, insurance companies, telecommunications companies, hospitals, and colleges. In total, 502 questionnaires were distributed, and 82.97 percent of the copies that were filled out and returned were used in the study. Descriptive statistics, correlation, and multiple regression were used to analyze the data. Organizational training and development and career planning, according to the study's findings, have a significant impact on employee involvement in their jobs and performance. As a result, Nepalese service sector organizations must make provisions of the budget for additional employee training and development programs. Similarly, it is necessary to provide employees with career development opportunities so that they can stay with the company for an extended period.